2009
DOI: 10.1128/aac.00952-08
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Daptomycin plus Ceftriaxone Is More Active than Vancomycin plus Ceftriaxone in Experimental Meningitis after Addition of Dexamethasone

Abstract: We examined the cerebrospinal fluid penetration of daptomycin after the addition of dexamethasone and its bactericidal efficacy with and without ceftriaxone in an experimental rabbit model of pneumococcal meningitis. The combination of daptomycin with ceftriaxone was the most efficacious regimen for pneumococcal meningitis. The previous addition of dexamethasone affected the antibacterial activity of daptomycin only marginally, either as monotherapy or combined with ceftriaxone, although the penetration of dap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
0
3

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 14 publications
0
19
0
3
Order By: Relevance
“…Treatment with daptomycin led to lower levels of inflammatory cytokines and possibly to less cortical brain damage and neuronal apoptosis than those for treatment with ceftriaxone alone (176,177). Although adjunctive treatment with dexamethasone did not result in a reduction of overall pneumococcal clearance from the CSF, daptomycin penetration into the inflamed meninges was reduced in the presence of adjunctive corticosteroid therapy (136).…”
Section: Nonbacteriolytic Antibioticsmentioning
confidence: 88%
“…Treatment with daptomycin led to lower levels of inflammatory cytokines and possibly to less cortical brain damage and neuronal apoptosis than those for treatment with ceftriaxone alone (176,177). Although adjunctive treatment with dexamethasone did not result in a reduction of overall pneumococcal clearance from the CSF, daptomycin penetration into the inflamed meninges was reduced in the presence of adjunctive corticosteroid therapy (136).…”
Section: Nonbacteriolytic Antibioticsmentioning
confidence: 88%
“…Furthermore, Gerber et al revealed that in a methicillin-susceptible S. aureus (MSSA) rabbit meningitis model the penetration of a single dose of 15 mg/kg of daptomycin was 5% into inflamed meninges versus 2% into noninflamed meninges (16). The addition of dexamethasone significantly reduced the penetration from 6% to 2% after a single 15-mg/kg dose of daptomycin into a rabbit pneumococcal meningitis model (12). Most recently, Riser et al reported on the CSF penetration of daptomycin dosed at 9 mg/kg/day in a 54-year-old patient with suspected MSSA meningitis.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, rifampin and clindamycin reduced the release of lipoteichoic acid and had a neuroprotective effect in an experimental rabbit model of pneumococcal meningitis (9,10). Furthermore, pretreatment with rifampin 1 h prior to ceftriaxone therapy limited the extent of brain injury (59), and the combination of daptomycin with ceftriaxone was shown to be more active than vancomycin plus ceftriaxone (18) in experimental pneumococcal meningitis in rabbits.…”
mentioning
confidence: 99%